Evaluation of Yeast Culture Supplementation on Milk Yield and Rumen Fermentation in Dairy Cows - A Field Study in Chhattisgarh - Shukla, Namita; Tiwari, Ashutosh; Sharma, Kranti; Yadav, Renu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Low milk yield remains a significant challenge for smallholder dairy farmers in Chhattisgarh, India, due to suboptimal nutrition and  inefficient rumen fermentation. This study evaluated the effects of dietary supplementation with Saccharomyces cerevisiae yeast culture  on milk production and rumen fermentation characteristics in lactating crossbred cows (30-60 DIM) under field conditions in Dhamtari  and Raipur districts. A total of 40 cows were randomly allocated into two groups: Control (basal diet only) and Treatment (basal diet plus  10 g/day of yeast culture) over a 90-day period. Results showed a statistically significant improvement (p
Keywords: Dairy cows; Milk yield; Rumen fermentation